Multidimensional Rasch Analysis of Gender Differences in Tes Intelegensi Kolektif Indonesia–Tinggi (TIKI-T) - Whisnu Yudiana; Airin Triwahyuni; Hery Susanto (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2023)
The empirical evidence on gender differences in the g-factor or general intelligence and various cognitive abilities remains contradictory. Some studies have found that there are no gender differences in general intelligence, while others have found differences between genders in verbal, spatial, and numerical abilities as measured by standardized cognitive tests. This study aims to examine the presence of differential item functioning (DIF) on standardized tests that measure verbal, numerical, and spatial/nonverbal abilities, as well as gender differences in item level. The multidimensional Rasch model was used to identify DIF based on four cognitive domains in the Tes Intelegensi Kolektif IndonesiaTinggi (TIKI-T) test. A total of 1,443 undergraduate students were tested. The results of the study showed that while there were several unbiased items, some items were clearly biased against males or females. The DIF was higher in the numerical and verbal subtests for female-male differences, while the DIF on male tests corresponded to spatial/nonverbal subtest performance. The theoretical and practical implications of the results are discussed.